Pengaruh Urbanisasi Terhadap Kemiskinan di Indonesia - Asmaryani, Wulan; Marta, Joan (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This research seeks to examine the impact of urban growth on poverty rates in Indonesia over the period of 1994-2023, taking the Human Development Index (HDI) and economic progress as control variables into account. The analysis was conducted using the ordinary least squares regression technique, utilizing both long-term and short-term perspectives (Error Correction Model). The findings indicate that, in the long run, the urban growth coefficient of 0.527062 exhibits a positive correlation with poverty but lacks significance (Prob. 0.2132 > 0.05). In contrast, in the short term, the urban growth coefficient of 0.9688 demonstrates a significant positive effect on variations in poverty rates (Prob. 0.0380 < 0.05). The HDI reveals a coefficient of -1.302436, indicating a substantial negative influence on poverty in the long term (Prob. 0.0239 < 0.05), although it is insignificant in the short term (Prob. 0.2431 > 0.05). Economic progress significantly and negatively impacts poverty, with a long-term coefficient of -0.316407 (Prob. 0.0062 < 0.05) and a short-term coefficient of -0.1968 (Prob. 0.0002 < 0.05). This study advocates for a more inclusive approach to urbanization management, enhancement of HDI, and pursuit of sustainable economic growth as viable strategies for alleviating poverty in Indonesia.